Analysis of Derivational and Inflectional Morpheme in Song's Lyrics of Adele Album - Evan Afri; Intan Maulina (International Journal of English and Applied Linguistics (IJEAL), 2021)
This research aims to find the derivative affixes and Inflection affixin "Song Adele Album". This study is a descriptive qualitative study. Researcher tries to find derived words, ending affixes and roots from words in Songs Adele Albums without using statistical calculations. In this study, the author used all words containing prefixes and suffixes as data. The data source is all parts of the word, which are the beginning of the song sung by Adele's album. The result of analyzing the data is that the derived affixes and affixes found in the song Adele album are -er, -en, -ing, -ly, -ment, -ness, -ness as suffixes, and the affixes are -d, -s, -ed, -ing, -es, -er, -est. From the conclusions of this study, the author suggests that in order to improve their vocabulary mastery, readers should apply derived words and affixes by decomposing words into roots and affixes, because they can get the structure of a word from a word , and also discover how words are constructed. By understanding the roots, readers can construct words themselves.